Changing practice of cardiac surgery in adult patients with congenital heart disease. Issue 2 (18th January 2005) - Srinathan, S K; Bonser, R S; Sethia, B; Thorne, S A; Brawn, W J; Barron, D J
Abstract : Objectives: To review 13 years' data from a unit for grown ups with congenital heart disease (GUCH) to understand the change in surgical practice. Methods: Records were reviewed of patients over 16 years of age undergoing surgery between 1 January 1990 and 31 December 2002 in a dedicated GUCH unit. Patients with atrial septal defects were included but not those with Marfan's syndrome or undergoing a first procedure for bicuspid aortic valves. Three equal time periods of 52 months were analysed. Results: Of 474 operations performed, 162 (34.2%) were repeat operations. The percentage of repeat operations increased from 24.8% (41 of 165) in January 1990–April 1994 to 49.7% (74 of 149) in September 1998–December 2002. Mortality was 6.3% (n  =  30). The median age decreased from 25.4 years (interquartile range 18.7) in January 1990–April 1994 to 23.9 (interquartile range 17.3) in September 1998–December 2002 (p  =  0.04). The proportion of patients with a "simple" diagnosis decreased from 45.4% (74 or 165) in January 1990–April 1994 to 27.5% (41 of 149) in September 1998–December 2002 (p  =  0.013). Pulmonary valve replacements in operated tetralogy of Fallot increased from one case in January 1990–April 1994 to 23 cases in September 1998–December 2002 and conduit replacement increased from five cases to 17. However, secundum atrial septal defect closures decreased from 35 cases to 14 (p < 0.0001). The estimated cost (not including salaries and prosthetics) incurred by an adult patient with congenital heart disease was £2290 compared with £2641 for a patient undergoing coronary artery bypass grafting. Conclusion: Despite the impact of interventional cardiology, the total number of surgical procedures remained unchanged. The complexity of the cases increased particularly with repeat surgery. Nevertheless, the patients do well with low mortality and the inpatient costs remain comparable with costs of surgery for acquired disease.